Coin sorter machine - Muhamad Nazir, Muhamad Nazif; Ismail, Mohd Fadzli (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Manual coin handling poses significant challenges for small businesses due to its inefficiency, inaccuracy and labour-intensive nature. It made even more difficult by the expensive and bulky nature of commercial sorting machines. This study addresses these issues by developing a low cost and compact prototype coin sorter machine designed for Malaysian coin denominations. The aim of this project is to design and fabricate a user-friendly sorting device that enhanced sorting accuracy and operational reliability. The methodology involved a structured design approach using SolidWorks for modelling and analysis, followed by material selection such as steel for the body and acrylic for coin trays. The prototype was then fabricated through cutting, joining, and assembly processes. Experimental results demonstrate that the coin sorter machine operates effectively, accurately distinguishing and sorting 5, 10, 20, and 50 cent coins using size-calibrated channels. The machine demonstrated reliable performance in terms of sorting speed, energy efficiency, and ease of use. In conclusion, the project proves the viability of an affordable automated coin sorter, offering improved productivity, cost savings and convenience for small-scale applications.